oard Composition, Ownership Structure and Dividend Payout Policy: Evidence from PSX-100 Index of Pakistan - MUHAMMAD NAVEED AHMAD; FARMAN ULLAH KHAN; YOUSAF KHAN (Journal of Business & Tourism, 2021)
The purpose of this study is to analyze the influence of board composition, ownership structure on dividend payout policy. Ordinary Least Square and Logistic regression models were applied to test the estimation in Pakistani KSE 100-index firms for the period of 2005 to 2014. Corporate Governance (board composition and ownership structure) were taken as independent variables, dividend payout / dividend decision as dependent variables. It is ascertained that the board size, executive director, institutional, foreign ownership and return on equity are significantly influenced on dividend payout /decision. Over study results evidenced that those firms who have higher profitable provide signal to the market to pay higher dividend in Pakistani firms and intended to resolve the agency problems issues.